The Influence of Green Trust on Purchase Decisions for Bottled Drinking Water (Amdk) - Adam Rizky Baihaki; Dudi Permana (Indonesian Journal of Business Analytics, 2025)
This study aims to determine and analyze the influence of green advertising, corporate social responsibility (CSR) activity, eco-label, and perceived value on purchase decisions, with green trust as a mediating variable in bottled drinking water (AMDK) consumers. This study uses a quantitative approach with a non-probability sampling method and a purposive sampling technique. The population in this study were bottled drinking water consumers domiciled in the DKI Jakarta area, and the sample used were respondents who had consumed bottled drinking water, with a total of 133 respondents. Data collection was carried out through an online questionnaire. Data were analyzed using the Structural Equation Modeling–Partial Least Square (SEM–PLS) method through SmartPLS software. The results of this study indicate that all independent variables, namely green advertising, CSR activity, eco-label, and perceived value, have a positive and significant influence on green trust. In addition, the green trust variable also has a positive and significant influence on purchase decisions. Furthermore, green trust is proven to play a significant role as a mediating variable in the relationship between green advertising, CSR activity, eco-label, and perceived value on purchase decisions.